(untitled) (Marketing Journal, 2026)
Abstract In the article is discussed the current social welfare financing mechanisms in the Republic of Uzbekistan, their effectiveness, and areas for improving their effectiveness. There is analyzed government strategies, institutional changes, and scientific approaches to improving financial support for social welfare. Attention is paid to the analysis of funding sources, digitalization of systems, and the implementation of international experience. Keywords: social security, efficiency, social security financing, digitalization.